Impact of vaccination on infection or death from COVID-19 in individuals with laboratory-confirmed cases: Case-control study - Hernández Bautista, Porfirio Felipe; Grajales Muñiz, Concepción; Cabrera Gaytán, David Alejandro; Rojas Mendoza, Teresita; Vallejos Parás, Alfonso; Santacruz Tinoco, Clara Esperanza; Alvarado Yaah, Julio Elias; Anguiano Hernández, Yu Mei; Sandoval Gutiérrez, Nancy; Jaimes Betancourt, Leticia (PloS one, 2023)
The objective of this study is to estimate the effectiveness of COVID-19 vaccines in people treated within the social security system whose vaccination status was reported to the epidemiological surveillance system. Case-control study. This was a case-control study conducted. The records of individuals with suspected cases of COVID-19 registered in the epidemiological surveillance system between February 1 and June 30, 2021, were studied. RT-qPCR was performed to determine SARS-CoV-2 infection; those with a positive result were considered cases, and those with a negative result were considered controls. The ratio between cases and controls was 1:1.3. The crude and adjusted vaccine effectiveness was considered the prevention of symptomatic infection and death and calculated as the difference between the dose and the risk, with a survival analysis among vaccinated people. A total of 94,416 individuals were included, of whom 40,192 were considered cases and 54,224 controls; 3,781 (4.00%) had been vaccinated against COVID-19. Vaccination also proved to be a protective factor against COVID-19, especially in the population who received a second dose (OR = 0.31; 95% CI 0.28-0.35). With the application of the vaccine, there was a protective effect against mortality (OR = 0.76; 95% CI 0.66-0.87). Disease prevention was higher for the BNT162-2 mRNA vaccine (82%) followed by the ChAdOx1 vaccine (33%). In the survival analysis, vaccination provided a protective effect. There was a positive impact of vaccines for the prevention of symptomatic COVID-19, with a second dose generating greater efficacy and a reduction in deaths.